2018
DOI: 10.20319/pijss.2018.42.330347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Service Learning and Educational Trips Instructional Strategies on Primary School Pupils’ Environmental Literacy in Social Studies in Oyo State, Nigeria

Abstract: The study, determined the effect of service learning and educational trips instructional strategies and moderating effect of school location and gender on primary school pupils' environmental literacy in social studies. The pretest, posttest, control group, quasiexperimental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
2
6
1
Order By: Relevance
“…Other authors have found that subjects themselves attribute low performance to low ability and to luck, and an improvement in performance -to motivation (task goal orientation), self-regulating behaviours, and to competence as a function of task characteristics (Oni, 2007). Gbadamosi (2012) showed positive correlations between the value given to the task and the perceptions of auto-efficacy and performance. Academic self-concept is at the base of future school success or failure, having been formed starting in early childhood education from peer contact and teacher attitude and expectations.…”
Section: Literature Reviewmentioning
confidence: 94%
See 1 more Smart Citation
“…Other authors have found that subjects themselves attribute low performance to low ability and to luck, and an improvement in performance -to motivation (task goal orientation), self-regulating behaviours, and to competence as a function of task characteristics (Oni, 2007). Gbadamosi (2012) showed positive correlations between the value given to the task and the perceptions of auto-efficacy and performance. Academic self-concept is at the base of future school success or failure, having been formed starting in early childhood education from peer contact and teacher attitude and expectations.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Oni (2007) and Omoegun (2007) averred that there is a significant difference between the rates of deviant behaviour among students from high and low family income. Also, Gbadamosi (2012) observed that when a child gets proper nutrition, health care, proper sewage and refuse disposal experience, and the ability to interact well with the environment, such child would not be found wanton in many spheres of life (Ugboma, 2002). In view of the general poverty level in Nigeria, the intention of this study is to determine whether there would be any significant difference in the environmental learning outcomes among students from high, medium and low parental income.…”
Section: Introductionmentioning
confidence: 99%
“…Somewhere the teacher's inability to handle all the contents satisfactorily due to her lack of confidence and knowledge in all areas of social science also appeared as an obstacle. Also lack of technological skills which could be used to create a better impact of the content delivery resulted in the student's discontent (Gbadamosi, T.V. (2018).…”
Section: Are You Satisfied By the Way The Content Is Delivered?mentioning
confidence: 99%
“…Marcus also explains further that service-learning is more basically concerned with empowering students with knowledge that can make them do permanent good for the interest of their communities. Service-learning's central components include: active participation, thoughtfully organized experiences, focus on community needs and school/community coordination, academic curriculum integration, structured time for reflection, opportunities for application of skills and knowledge, extended learning opportunities, build self-confidence and development of a sense of caring for others (Trane & Zane, 2014, Gbadamosi, 2012).…”
Section: Service Learning and University Educationmentioning
confidence: 99%
“…Improvement in knowledge and skills, sense of caring and increase self-confidence are as a result of teaching through service learning strategy (Trae & Zane, 2014). Four-stage service-learning processes are (a) preparation, (b) implementation, (c) assessment/reflection, and ddemonstration/celebration (Gbadamosi, 2012;Trae & Zane, 2014).…”
Section: People: International Journal Of Social Sciences Issn 2454-5899mentioning
confidence: 99%